THE IMPLIKASI GAYA KEPEMIMPINAN TERHADAP KETERIKATAN KERJA PADA PUSAT PENELITIAN DAN PENGEMBANGAN SUMBER DAYA AIR - Metha Djuwita Supriatna (Jurnal Administrasi Negara, 2018)
The purpose of this research was to analyze the effect of leadership style to work engagement at the Centre for Water Resources Research and Development, Ministry of Public Works and Public Housing. Descriptive and verivicative method are used in this study, with data used in this research was collected by using questionnaire. The respondents were 100 civil servant officer of the Centre for Water Resources Research and Development selected proportionally from each unit of the Centre. The sampling method was convenience sampling. The result of this research showed that situational leadership style at the Centre is selling dimension of leadership style. Findings show that work engagement at the Centre is relatively high. As expected, there is significant effect of the leadership style on work engagement. The relatively medium variance founded from linier effect of leadership styles on work engagement. This implies on the relevance and need for further studies in the future.